Laparoscopic treatment of inguinal hernia in female children – national experience - Risteski, Toni (Lietuvos chirurgija, 2021)
Background. Although, laparoscopic inguinal hernia repair in children is gaining ground as a safe, feasible, and popular method, still many pediatric surgeons continue to debate its safety, efficacy, and cosmesis in comparison with conventional open repair. Materials and methods. This was a prospective clinical study, that elaborated 98 female children aged 1–14 with clinically diagnosed indirect inguinal hernia. Equal proportions of 49 children were treated via laparoscopic (PIRS) either conventional open repair (OR). Outpatient clinic follow up was performed regardless of the type of the intervention, on the 7th day and 6 weeks after discharge. Results. The mean age of children in PIRS vs. OR group was 5.3±2.7 vs. 5.9±3.3 years. There was no significant differences between the groups related to age (p = 0.4221), weight (p = 0.5482), family history (p = 0.5377), and residency rural/urban (p = 0.3161). The average length of unilateral vs. bilateral PIRS repair (29.5±6.8 vs. 43.6±7.2 min) was significantly shorter than OR (44±4.2 vs. 97±8.1 min) for consequently p = 0.0023 vs. p = 0.00001. The post-operative hospitalization after PIRS repair was 14.1±3.1 hours and was significantly shorter compared to OR – 44±4.2 hours (p = 0.00001). In OR group, 4 (8.2%) children had postoperative nausea compared to none in PIRS group. Significantly bigger cosmetic satisfaction was found in PIRS compared to OM group (p = 0.0001). Conclusion. With due respect to OR as a gold standard, the proven advantages of PIRS are motivation for further improvement of this technique for the purpose of treatment of inguinal hernia of female children.